2017
DOI: 10.22278/2318-2660.2016.v40.n2.a1980
|View full text |Cite
|
Sign up to set email alerts
|

Perfil Epidemiológico Dos Usuários De Um Centro De Testagem E Aconselhamento Da Bahia

Abstract: Os Centros de Testagem e Aconselhamento realizam diagnóstico e ações preventivas para doenças sexualmente transmissíveis, oferecendo testagem sorológica para HIV, sífilis e hepatites virais B e C. O objetivo da pesquisa foi traçar o perfil epidemiológico dos usuários de um Centro de Testagem e Aconselhamento da Bahia no período de 2006 a 2012, em relação a características sociodemográficas, situações de vulnerabilidade individual e prevalência de infecções sexualmente transmissíveis. Para tanto, foi rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
0
0
10

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 0 publications
1
0
0
10
Order By: Relevance
“…The Basic Health Units are important interlocutors of TCC/ SAS, as its professionals have closer contact with the patients and can do the testing or direct the person to the TCC for the appropriate conducts. In this sense, the present study observed that the main reason for attending the TCC/SAS occurred due to referral to another health service, as well in other studies 21,22 . However, the search for assistance in the Health Unit must be occurring late, and the referral of the patient to the TCC/SAS or the time spent by the patient to attend the consultation must be more extended, as many arrived to confirm the diagnosis and monitoring with low TCD4+ lymphocyte values and detectable viral load.…”
Section: Discussionsupporting
confidence: 87%
“…The Basic Health Units are important interlocutors of TCC/ SAS, as its professionals have closer contact with the patients and can do the testing or direct the person to the TCC for the appropriate conducts. In this sense, the present study observed that the main reason for attending the TCC/SAS occurred due to referral to another health service, as well in other studies 21,22 . However, the search for assistance in the Health Unit must be occurring late, and the referral of the patient to the TCC/SAS or the time spent by the patient to attend the consultation must be more extended, as many arrived to confirm the diagnosis and monitoring with low TCD4+ lymphocyte values and detectable viral load.…”
Section: Discussionsupporting
confidence: 87%
“…Além da confiança no (a) parceiro (a), já citada, outros fatores são destacados pela literatura como promotores do sexo inseguro como o uso de drogas lícitas e ou ilícitas, a iniciação precoce da vida sexual, múltiplas parcerias sexuais e o desejo de melhorar o desempenho e prazer durante a relação sexual (FERREIRA et al,2016;HARTMAN;CESAR, 2013).…”
Section: Discussionunclassified
“…O álcool, substância mais utilizada no público pesquisado, principalmente pelos homens, por se tratar de uma droga lícita e de fácil acesso, é um dos principais inimigos da prática saudável da sexualidade (MOURA et al,2018). Outro estudo também encontrou maior uso de álcool e outras drogas entre os homens, sendo este o dobro em comparação com as mulheres (FERREIRA et al,2016).…”
Section: Discussionunclassified
“…Com isso, faz-se necessário que todos os profissionais de saúde envolvidos façam aconselhamentos abrangentes, valendo-se de histórias sexuais atendidas anteriormente, e tenham a atitude de rastrear as IST na população (26) . para a prevenção das IST.…”
Section: Discussionunclassified